The Influence of Tax Rates and Foreign Ownership on Corporate Decisions to Implement Transfer Pricing Policies: An Empirical Study of Consumer Non-Cyclicals Companies Listed on the Indonesia Stock Exchange - Felisa, Heni; Chandrarin, Grahita (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study aims to analyze the influence of tax rates and ownership on corporate decisions to implement transfer pricing policies. Transfer pricing has become a common strategic mechanism used by multinational corporations to reallocate profits between affiliated entities across various tax jurisdictions, and ultimately with the aim of minimizing tax liabilities and maximizing global after-tax profits. The objects of this study were companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange during the observation period. This study uses a quantitative approach, analyzing secondary data from companies’ annual financial reports, and employs multiple linear regression to examine the influence of tax rates and foreign ownership on corporate decisions to implement transfer pricing policies. The results show that tax rates have a significant and positive influence on transfer pricing, indicating that companies are more likely to implement transfer pricing when the tax burden is high. Conversely, foreign ownership does not show a significant influence on transfer pricing decisions, indicating that the presence of foreign shareholders does not inherently encourage transfer pricing practices. However, simultaneous testing indicates that tax rates and foreign ownership together have a significant influence on corporate decisions to implement transfer pricing policies.